Assessing Career Satisfaction and Trajectory Among Dental Professionals: 10 Years Repeated Cross-Sectional Analysis - Meyassara Samman; Shahad B. Alsharif (International Dental Journal)
Introduction: Dentists career satisfaction can significantly affect their quality of life and the quality of healthcare services provided to their patients. The aim of this 10-year repeated cross-sectional study is to assess career satisfaction among dentists and investigate its influencing factors. Methods: Participants were distinct cohorts of dentists (n = 115) who graduated from King Abdulaziz University, Jeddah, in 2013, surveyed at 2 time points: upon graduation and 10 years later (2023). Data were collected through anonymous self-administered questionnaires. Descriptive statistics and bivariate analyses were performed, with the significance level set at <0.05. The distinct cohorts allowed for population-level insights but introduced variability that may affect longitudinal comparability. Results: The study included distinct cohorts of 90 respondents at each survey period (response rate was 78.3%). Of these, 68.9% were satisfied with their careers. Those who were satisfied were more likely to have a higher GPA (P value = .002), have a postgraduate degree (P value = .002), and practice in an academic institute (P value < .001). Only 31.1% felt their current career status was very aligned with their expectations set 10 years ago. (56.5%) were either considering changing their career away from dentistry or still unsure. Although 58.9% were working as full-time dentists, 45.6% of them are not planning to continue as they have the desire for early retirement. In fact, 7.8% have already quit dentistry and shifted to other professions. Only 15.6% chose dentistry because they were passionate about it. (52.2%) are planning to start a new full-time career outside dentistry. Conclusions: GPA, higher education, and work institutions influenced satisfaction and career alignments. Unsatisfied dentists are interested in establishing new careers in other fields consistent with Saudi Vision 2030. Clinical relevance: Investigation of students’ motivation by academic advisors is encouraged to guide them to achieve their expected goals and, thus, career satisfaction.